The Influence of Institutional Capacity on the Implementation of Smart Villages in the Development of Village - Rahmawati, Rita; Jumarto; Alpy, Math; Syafii, Muhammad; Satispi, Evi; Salam, Rahmat (Indonesian Journal of Social Research (IJSR), 2025)
A smart village is a village whose people use technology and digital innovation in their daily lives. Implementing the smart village concept in rural development requires adequate village institutional capacity. Low institutional capacity causes an organization to lack the capacity to manage development and provide services. In general, the capacity of village organizations in almost all villages in Indonesia was relatively low, so the successful implementation of the bright village concept in village development requires more time. Regarding this problem, this study aimed to test whether or not village institutional capacity influences the implementation of smart villages in village development. The location of the study was chosen as Sembalun Bumbung Village, Sembalun District, East Lombok Regency, West Nusa Tenggara Province, Indonesia. This study used a quantitative approach with an associative research method, namely testing the influence of village institutional capacity variables on smart village implementation variables. Data collection techniques used questionnaires and literature studies. The research instrument has been tested through validity and reliability tests. The data analysis technique used analysis using the Pearson correlation test (product-moment). The study results showed that the village institutional capacity variable affects the smart village implementation variable with a determination coefficient of 74.30%, which indicates a strong relationship between the two variables. These results are crucial for understanding the dynamics of smart village implementation. The research results also found that several factors influenced the success of implementing smart villages: infrastructure, networking, and community participation.